Acceptability and Feasibility of Peer Specialist-Delivered Virtual Reality Job Interview Training for Individuals with Serious Mental Illness: A Qualitative Study. Issue 3 (18th August 2021) - Üstel, Pınar; Smith, Matthew J.; Blajeski, Shannon; Johnson, Jeffery M.; Butler, Valerie G.; Nicolia-Adkins, Johanna; Ortquist, Monica J.; Razzano, Lisa A.; Lapidos, Adrienne
Abstract: This study explored peer specialists' perspectives on delivering vocational interventions, especially Virtual Reality Job Interview Training (VR-JIT). Five focus groups of peer specialists ( N = 34) explored their beliefs about vocational services, including VR-JIT. We trained eight peer specialists to be VR-JIT "instructors" and interviewed them about using VR-JIT in their mental health practice. Generally, participants discussed tailoring their vocational services to include sharing their story of recovery. Specifically, participants perceived VR-JIT as acceptable and feasibly implemented within their practice. Overall, participants viewed VR-JIT as a higher level of service and they would be uniquely qualified to support consumers using the tool.